Trajectories and associations between depression and physical activity in patients with cardiovascular disease during participation in an internet-based cognitive behavioural therapy programme. (5th August 2020) - Johansson, Peter; Svensson, Erland; Andersson, Gerhard; Lundgren, Johan
Abstract: Background: There is a lack of knowledge about internet-based cognitive behavioural therapy in patients with cardiovascular disease, and its effects on depressive symptoms and physical activity. Aim: To examine trajectories of depressive symptoms and physical activity, and to explore if these trajectories are linked with the delivery of internet-based cognitive behavioural therapy. Methods: A secondary-analysis of data collected in a randomised controlled trial that evaluated the effects of a 9-week internet-based cognitive behavioural therapy programme compared to an online discussion forum on depressive symptoms in cardiovascular disease patients. Data were collected at baseline, once weekly during the 9-week intervention period and at the 9-week follow-up. The Montgomery Åsberg depression rating scale – self-rating (MADRS-S) was used to measure depressive symptoms. Two modified items from the physical activity questionnaire measuring frequency and length of physical activity were merged to form a physical activity factor. Results: After 2 weeks the internet-based cognitive behavioural therapy group had a temporary worsening in depressive symptoms. At 9-week follow-up, depressive symptoms ( P < 0.001) and physical activity ( P = 0.02) had improved more in the internet-based cognitive behavioural therapy group. Only in the internet-based cognitive behavioural therapy group, was a significant correlation ( r = –0.39, P = 0.002) between changes in depressive symptoms and changes in physical activity found. Structural equation analyses revealed that internet-based cognitive behavioural therapy decreased depressive symptoms, and that a decrease in depression, in turn, resulted in an increase in physical activity. Conclusions: Internet-based cognitive behavioural therapy was more effective than an online discussion forum to decrease depressive symptoms and increase physical activity. Importantly, a decrease in depressive symptoms needs to precede an increase in physical activity.